2022
DOI: 10.1002/zaac.202100331
|View full text |Cite
|
Sign up to set email alerts
|

Three Zn(II) coordination polymers as dual‐responsive luminescent probes for highly selective detection of Fe3+ cation and MnO4 anion

Abstract: Effective detection of Fe 3 + cation and MnO 4À anion from water are desirable. As another way to solve this problem, three Znbased luminescent coordination polymers (LCPs), and [Zn(3bpat)(5-mip)](3) (3-bpat = N,N'-bis(3-pyridylamide)-3,4thiophene, 1,3-H 2 bdc = isophthalic acid, 5-H 2 hip = 5-hydroxyisophthalic acid, 5-H 2 mip = 5-methylisophthalic acid), were successfully prepared as optical sensors to detect target analytes. Three LCPs were characterized by single crystal X-ray diffraction, powder X-ray dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…All species showed a good fluorescence quenching response to Fe(III) and MnO 4 − with high selectivity and sensitivity, the DLs for both analytes being in the nanomolar range. Moreover, cation and anion competition experiments indicated that the luminescence quenching response of both analytes were almost unaffected by interfering ions [ 57 ].…”
Section: Zinc(ii) Carboxylate Coordination Polymers Developed For Dif...mentioning
confidence: 99%
“…All species showed a good fluorescence quenching response to Fe(III) and MnO 4 − with high selectivity and sensitivity, the DLs for both analytes being in the nanomolar range. Moreover, cation and anion competition experiments indicated that the luminescence quenching response of both analytes were almost unaffected by interfering ions [ 57 ].…”
Section: Zinc(ii) Carboxylate Coordination Polymers Developed For Dif...mentioning
confidence: 99%